(untitled) (Revista Apotheke, 2022)
This article shows reflexive processes developed in classes of teaching practices on Visual Arts education program during the COVID-19 pandemic. The construction of the teaching identity is linked to the singularities generated between the students’ relationships with the teaching practices in Visual Arts, in addition to the learning carried out in the teaching learning classes. We articulate these questions with reflections about cultural aspects that involve teaching and an idea of Shared Teaching. We propose to show issues that go beyond the impositions made on the COVID-19 pandemic, like choices, conflicts and movements that are made during teaching practices on the Art Visual education program. The listening and sharing exercises, with some changes in the itinerary, were carried out in educational and internship contexts, as exercises that involve welcoming and building of strategies for the professional education training at the university.